Sexuality and psychoanalysis : philosophical criticisms - Vleminck, Jens de; Dorfman, Eran (Figures of the unconscious, 2010)
The relationship between sexuality and psychoanalysis can be described in terms of an old and stormy love affair. The same can be said about the relationship between psychoanalysis and philosophy. It is precisely this fascinating 'love triangle'' that the present volume of essays aims to explore. A diverse group of philosophers and psychoanalysts reflected on the concept of sexuality in Freudo-Lacanian psychoanalysis. The result is a stimulating collection of essays where the role of sexuality in psychoanalysis is scrutinized from a philosophical point of view. This volume does more than merely.